2018
DOI: 10.1108/ijhrh-02-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Exploring community capacity: Karen refugee women’s mental health

Abstract: PurposeThe purpose of this paper is to describe Karen refugee women’s experience of resettlement and the factors which structured community capacity to support their mental health and well-being.Design/methodology/approachA postcolonial and feminist standpoint was used to bring Karen women’s voice to the knowledge production process. Data were collected through ethnographic field observation, in-depth semi-structured individual and focus group interviews with Karen women as well as healthcare and social servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…The centrality of gender in determining health-seeking behavior was reflected in the way women often de-prioritized their own health, leisure and self-care, and healthcare-seeking in favor of their partners’ and children’s [ 3 , 32 , 35 ]. Another common experience during resettlement was the inability to care for one’s own health and wellbeing due to childcare roles and responsibilities [ 32 , 36 , 37 ]. Women found it challenging to find time to access medical services [ 36 ] or practice self-care through leisure or physical activity [ 38 ] as the absence of extended family limited options for childcare, a responsibility seemingly borne largely by women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The centrality of gender in determining health-seeking behavior was reflected in the way women often de-prioritized their own health, leisure and self-care, and healthcare-seeking in favor of their partners’ and children’s [ 3 , 32 , 35 ]. Another common experience during resettlement was the inability to care for one’s own health and wellbeing due to childcare roles and responsibilities [ 32 , 36 , 37 ]. Women found it challenging to find time to access medical services [ 36 ] or practice self-care through leisure or physical activity [ 38 ] as the absence of extended family limited options for childcare, a responsibility seemingly borne largely by women.…”
Section: Resultsmentioning
confidence: 99%
“…This practice may affect consent, confidentiality, and transparency, particularly when seeking services or information for issues may be personal or stigmatized such as sexual and reproductive health, sexual or gender-based violence, or mental health [ 3 , 34 , 56 ]. When working with Karen refugees (an ethnic group from Myanmar), Clark (2018) found that even when professional interpreters were available to women in their resettlement communities, some were not comfortable arranging for their services, or were hesitant to disclose personal information, particularly if there was a discrepancy in gender, ethnic background, or sexual orientation between the interpreter and the patient [ 37 ]. Participants in a study by Donelly and colleagues (2011) consistently identified the need for translated materials on mental health and other health services as a means to improve access to healthcare [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a considerable amount of literature has been published on the extensive limitations of physical refugee camps which have outweighed the perceived benefits. These limitations include but are not limited to: mental health such as psychological distress [12,15,30], greater domestic violence towards women, illnesses amongst children under 5 [14], lack of dignity and normalcy [27], and poor health conditions such as chronic illness and spread of infectious diseases [18,36]. The UNHCR has published policies and standards for designing and implementing refugee camps or settlements, however, UNHCR prefers alternatives to camps, provided they protect and assist people of concern effectively [2].…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%
“…Domination of women in domestic work has a greater obligation than childcare and other household activities. However, they lack employment opportunities that can become entrepreneurship as a more profitable option for their family's income [7][8][9][10]. Women's training groups are the first step in increasing social and economic capacity.…”
Section: Introductionmentioning
confidence: 99%